The Influence of Organizational Climate, Leadership, and Trust on Knowledge Sharing Behavior of Vocational Teachers - Caniago, Tarida Alfiah; Febriantina, Susan; Maulida, Ervina (Politeknik Assalaam Surakarta, 2025)
Knowledge-sharing behavior in the school environment has a crucial role in efforts to improve the quality of the learning process and the performance of teachers. This study was directed to analyze the influence of organizational climate, leadership style, and level of trust on knowledge sharing behavior among teachers of State Vocational Schools in Bambu Apus Village, East Jakarta. The method applied was in the form of a survey by distributing questionnaires to 126 teachers from three State Vocational Schools in the area. The collected data was then processed using a quantitative descriptive approach with the help of Smart PLS software to see the relationship between the variables studied. The results of the hypothesis test show that organizational climate, leadership, and trust play a significant role in influencing knowledge sharing behavior. However, this study also found a sense of distrust between teachers regarding information confidentiality and a lack of optimal innovation in learning leadership. Therefore, it is suggested that communication, cooperation, and trust in the school environment can be improved to support the creation of a more effective knowledge-sharing culture.